2002
DOI: 10.1128/jvi.76.12.6155-6163.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Aquatic Alphaviruses, Salmon Pancreas Disease Virus and Sleeping Disease Virus, by Using Genome Sequence Analysis, Monoclonal Reactivity, and Cross-Infection

Abstract: Cell culture isolates of salmon pancreas disease virus (SPDV) of farmed Atlantic salmon and sleeping disease virus (SDV) of rainbow trout were compared. Excluding the poly(A) tracts, the genomic nucleotide sequences of SPDV and SDV RNAs include 11,919 and 11,900 nucleotides, respectively. Phylogenetic analysis places SPDV and SDV between the New World viruses of Venezuelan equine encephalitis virus and Eastern equine encephalitis virus and the Old World viruses of Aura virus and Sindbis virus. When compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
176
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(181 citation statements)
references
References 48 publications
5
176
0
Order By: Relevance
“…To change the site between nsP1 and nsP2 from HAGA2GVVE to HAEA2GVVE, the site between nsP2 and nsP3 from TAGS2APSY to TAES2APSY, and the site between nsP3 and nsP4 from RAGA2YIFS to RAEV2YIFS, specific primers containing the desired mutations were used (bolded residues highlight the mutations made at the cleavage site). 2 The templates were clones P1234, P123, P23, and P12. All mutations were verified by sequencing, and the mutated clones were designated as P1 ∧ 234, P12 ∧ 34, P123 ∧ 4, P1 ∧ 23, P12 ∧ 3, P1 ∧ 2, and P2 ∧ 3 ( ∧ indicates the mutated site).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To change the site between nsP1 and nsP2 from HAGA2GVVE to HAEA2GVVE, the site between nsP2 and nsP3 from TAGS2APSY to TAES2APSY, and the site between nsP3 and nsP4 from RAGA2YIFS to RAEV2YIFS, specific primers containing the desired mutations were used (bolded residues highlight the mutations made at the cleavage site). 2 The templates were clones P1234, P123, P23, and P12. All mutations were verified by sequencing, and the mutated clones were designated as P1 ∧ 234, P12 ∧ 34, P123 ∧ 4, P1 ∧ 23, P12 ∧ 3, P1 ∧ 2, and P2 ∧ 3 ( ∧ indicates the mutated site).…”
Section: Methodsmentioning
confidence: 99%
“…Some alphaviruses are capable of causing encephalitis in humans or domestic animals, whereas others may cause fever and arthritis (1). Recently, alphaviruses pathogenic for fish have been discovered (2), indicating that the biological diversity and significance of alphaviruses is greater than previously anticipated. The alphaviruses best studied at the molecular level are Semliki Forest virus (SFV) 1 and Sindbis virus.…”
mentioning
confidence: 99%
“…Last, the aquatic alphaviruses comprise two groups, Southern elephant seal virus and salmon pancreas disease virus (SPDV) (6,7). SPDV and its subtype sleeping disease virus are distantly related to all other alphaviruses (7).…”
mentioning
confidence: 99%
“…This was later supported by the isolation of the virus from cases of pancreas disease that affected salmon in Norway (4) and Scotland (13). SPDV and sleeping disease virus (SDV) are closely related isolates of the same virus species, and the name salmonid alphavirus was proposed (15). Genetic analysis of the salmonid alphavirus from Norway revealed that it formed a distinct subtype, separate from both previously reported subtypes, and was named Norwegian salmonid alphavirus (8).…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, the virus was classified in 2008 into six subtypes; SPDV or subtype 1 (SAV1) had been isolated from Atlantic salmon in Ireland and the UK whilst SDV or subtype 2 (SAV2) had been isolated from freshwater rainbow trout in the UK, France, and Germany (2). Previous reports, subsequently showed that Norwegian strains belonged to a distinct subtype now referred to as NSAV or SAV3 (8,15), and a more extensive study identified three further subtypes: SAV4, SAV5, and SAV6 (5).…”
Section: Introductionmentioning
confidence: 99%